Propionibacterium acnes Types I and II Represent Phylogenetically Distinct Groups - McDowell, Andrew (American Society for Microbiology, 2005)
Although two phenotypes of the opportunistic pathogen Propionibacterium acnes (types I and II) have been described, epidemiological investigations of their roles in different infections have not been widely reported. Using immunofluorescence microscopy with monoclonal antibodies (MAbs) QUBPa1 and QUBPa2, specific for types I and II, respectively, we investigated the prevalences of the two types among 132 P. acnes isolates. Analysis of isolates from failed prosthetic hip implants (n = 40) revealed approximately equal numbers of type I and II organisms. Isolates from failed prosthetic hip-associated bone (n = 6) and tissue (n = 38) samples, as well as isolates from acne (n = 22), dental infections (n = 8), and skin removed during surgical incision (n = 18) were predominately of type I. A total of 11 (8%) isolates showed atypical MAb labeling and could not be conclusively identified. Phylogenetic analysis of P. acnes by nucleotide sequencing revealed the 16S rRNA gene to be highly conserved between types I and II. In contrast, sequence analysis of recA and a putative hemolysin gene (tly) revealed significantly greater type-specific polymorphisms that corresponded to phylogenetically distinct cluster groups. All 11 isolates with atypical MAb labeling were identified as type I by sequencing. Within the recA and tly phylogenetic trees, nine of these isolates formed a cluster distinct from other type I organisms, suggesting a further phylogenetic subdivision within type I. Our study therefore demonstrates that the phenotypic differences between P. acnes types I and II reflect deeper differences in their phylogeny. Furthermore, nucleotide sequencing provides an accurate method for identifying the type status of P. acnes isolates.